The novel use of a SenseCam and accelerometer to validate training load and training information in a self-recall training diary. Issue 4 (16th February 2016) - O. Connor, Siobhan; McCaffrey, Noel; Whyte, Enda; Moran, Kieran
Abstract: Self-recall training diaries are a frequently used tool to quantify training load and training information. While accelerometers are predominantly used to validate training diaries, they are unable to validate contextual training information. Thus this study aimed to examine the novel use of data fusion from a wearable camera device (SenseCam) and accelerometer to validate a self-recall training diary. Thirty participants filled in a training diary for 1 day while simultaneously wearing a SenseCam and accelerometer. The training diary was validated using Bland–Altman plots, Spearman's rank-order correlation, percentage agreement and κ measure of agreement between the diary and the SenseCam and accelerometer. The results demonstrated overall agreement, and no bias, between the training diary and the accelerometer for training intensity, and the SenseCam for duration of activity and travel time. A positive correlation was found for duration ( r  = 0.82, P  < 0.001) and intensity ( r  = 0.67, P  < 0.001). Hundred per cent agreement was found between the SenseCam and training diary for activity, training surface and footwear ( κ  = 1, P  < 0.0001), with a lower agreement noted for sports played (97.3%, κ  = 0.91, P  < 0.0001). The self-recall training diary was found to be a valid measure of capturing training load and training information using the combined wearable camera device and accelerometer.